The Universal Thermal Climate Index (UTCI) applications for microclimatic analysis in urban thermal environments. Case study; Oasis University campus, Algeria - Djaghrouri, Djamila; Boudjellal, Lazhar; Afren, Roumaissa; Benabbas, Moussadek (Technium Social Sciences Journal, 2023)
This work on outdoor thermal comfort tends to highlight and affirm the contribution of vegetation to outdoor thermal comfort in a climatically hostile environment by being very hot and dry, this effect of creating a more forgiving microclimate in terms of thermal atmosphere was highlighted by simulations and in situ measurements, in a semi-open public space with a set of mature ficus retusa trees that we cut later, in this way, it gives us an unexpected and important opportunity for an intangible conclusion on this thermal contribution by means of a comparison, within the same space, in other words, with the same morphological characteristics but in two different states; case "A" with the presence of trees and case "B" after these same trees have been cut. This led us to deduce the influence of persistent vegetation on thermal comfort in such an environment; the measurements were made before and just after cutting the trees. The comfort index (UTCI) was calculated from microclimatic factors, themselves dependent on morphological indices, the measurements carried out highlighted the variations in the comfort index, that is, an indicator of the thermal comfort in both cases. In the end, this confirms the great influence of the trees shade on the outdoor thermal comfort in a public space located at the university campus of Biskra.